Cathepsin S and Protease-Activated Receptor-2 Drive Alloimmunity and Immune Regulation in Kidney Allograft Rejection - Lei, Yutian; Ehle, Benjamin; Kumar, Santhosh V.; Müller, Susanne; Moll, Solange; Malone, Andrew F.; Humphreys, Benjamin D.; Andrassy, Joachim; Anders, Hans-Joachim (Frontiers in Cell and Developmental Biology, 2020)
Alloantigen presentation is an essential process in acute allorejection. In this context, we speculated on a pathogenic role of cathepsin S (Cat-S), a cysteine protease known to promote antigenic peptide loading into MHC class II and to activate protease-activated receptor (PAR)-2 on intrarenal microvascular endothelial and tubular epithelial cells. Single cell RNA sequencing and immunostaining of human kidney allografts confirmed Cat-S expression in intrarenal mononuclear phagocytes. In vitro, Cat-S inhibition suppressed CD4+ T cell lymphocyte activation in a mixed lymphocyte assay. In vivo, we employed a mouse model of kidney transplantation that showed preemptive Cat-S inhibition significantly protected allografts from tubulitis and intimal arteritis. To determine the contribution of PAR-2 activation first Balb/c donor kidneys were transplanted into Balb/c recipient mice without signs of rejection at day 10. In contrast, kidneys from C57BL/6J donor mice revealed severe intimal arteritis, tubulitis, interstitial inflammation, and glomerulitis. Kidneys from Par2-deficient C57BL/6J mice revealed partial protection from tubulitis and lower intrarenal expression levels for Fasl, Tnfa, Ccl5, and Ccr5. Together, we conclude that Cat-S and PAR-2 contribute to immune dysregulation and kidney allograft rejection, possibly involving Cat-S-mediated activation of PAR-2 on recipient parenchymal cells in the allograft.